An In Vivo Model for Studying Platelet Aggregation and Disaggregation - Page, C P; Paul, W; Morley, J (Thrombosis and Haemostasis, 1982)
A simple minimally invasive technique has been developed for the continuous monitoring of 111-Indium labelled homologous platelets in the thoracic (C1) and abdominal (C2) regions of experimental animals. The effects of the aggregatory agents adenosine diphosphate (ADP), collagen and platelet activating factor (PAF) and the anti-aggregatory agent, prostacyclin (PGI2) have been studied in the guinea-pig. Administration of ADP, collagen or PAF produces an increase in counts in C1, a decrease in counts in C2, and hence an increase in the ratio C1/C2. The rise in C1/C2 is more protracted after collagen administration than after ADP or PAF. PGI2 (50-500 ng/kg) reduces the response to ADP. The present technique is both simple, reproducible and although the present experiments are in the presence of heparin, the technique remains functional in the presence of minimal heparin, thus making it a suitable method for studies of platelet function and the evaluation of anti-aggregatory agents in vivo.
Keywords: Platelets; In vivo aggregation; 111-Indium